Learners’ perceptions of learning English through metaphors / Ervinna Luk Yee Woon - Ervinna , Luk Yee Woon (2016)
Learners and teachers often hold deep beliefs about language learning (Mariani, 2010) resulting in complexities based on attitudes, experiences and expectations (Riley, 2009). Effective language learning can potentially take place when the learners’ needs are met by the teachers through different classroom approaches. In the context of postgraduate teaching, learners come from various nationalities. Therefore, it is crucial to understand their perceptions on what constitutes language learning process and language teachers’ roles, especially in various socio-cultural educational settings (Borg, 2006) to ensure successful implementation of theoretical teaching methodologies (Sykes, 2011). Perception studies, however, revealed that examining the metaphors used by second language (L2) or foreign language learners are still under-explored. This research aims to tap into the cognition of postgraduates on their experiences and perceptions of learning English and the roles of language teachers using the indirect means of eliciting metaphorical responses from the participants. This study employs metaphor analysis as a significant educational and applied linguistics research tool in listening to the personal ‘voice’ of learners’ experiences. Metaphor-elicited questionnaires and retrospective interviews were conducted with 47 postgraduates from a Malaysian higher learning institution, mostly from the Faculty of Languages and Linguistics and a few from the Faculty of Medicine. A thematic analysis was conducted on the metaphorical expressions and entailments given for the learning dimensions and teacher roles. The qualitative analysis revealed that a majority of postgraduate learners shares metaphors of Cognitivist learning dimension, depicting learning English from a Cognitive perspective (thinking process). The major emerging themes that derived are ‘Internal’ and ‘External’ goals. A minority of postgraduate learners express metaphors under the Behaviourist paradigm, reflecting learning English as a repetitive, skill-acquisition process. None seem to conceive learning English as a social process under the Situative learning dimension. These results are complimented with the metaphors provided by the same participants on their views of a language teacher’s roles. A majority of the learners perceived language teachers as a ‘Provider’ and ‘Instructor’, while very few perceived them as a ‘Co-worker’ and none as a ‘Culture Transmitter’. The findings from these metaphors serve as stepping stones and insights to broader curriculum design in postgraduate teaching and learning, taking into considerations the learners’ personal language learning experiences.